Identifying FEG Standard through a Performance Study of Industrial Fans in Thailand - P. Tantakitti (2018)
© 2015 The Authors. Published by Elsevier Ltd. In Thailand, fans industry has a significant market worth of USD 50 million. They are commonly used in the ventilation system of a building. However, most of the locally made fans have not been certified by any organizations and tend to be inefficient, currently taking up on average 25 percent of the building's total energy consumption. As a result, the gross energy demand of the nation is wastefully high. In this study, we aim to establish a standard for the industrial fan efficiency which upon enforcement can lead to reduction of energy consumption by promoting manufacturing of competitively efficient equipment. In order to set a standard, we first surveyed the fan market in Thailand and found that the majority of the fans used are made in the country and with a capacity below 34,000 CMH. Fans are randomly chosen for the study and their Fan Efficiency Grades (FEGs) are determined through a performance testing in a chamber designed and built in-house for a maximum capacity of 34,000 CMH at 22 kW, following the ISO5801-2007: Industrial Fans-Performance Testing Using Standardized Airways. The comparisons between the FEGs of Thailand made fans and those of international model as well as an evaluation against the standard set by ASHRAE point out necessity for improvement in efficiency of locally made fans